BETWEEN MOSCOW AND NATO: TÜRKIYE'S STRATEGIC HEDGING IN A MULTIPOLAR WORLD - Erdurmaz, Ali Serdar; Yulianti, Dina (Intermestic: Journal of International Studies, 2025)
This article investigates the strategic motivations behind the evolving relationship between Türkiye and Russia, analyzing key diplomatic, economic, military, and energy dynamics. Although Türkiye is a NATO member, its increasingly independent foreign policy—driven by national interests and energy dependency—has allowed it to maintain close ties with Moscow despite growing tensions between Russia and the West. Conversely, Russia views Türkiye as a valuable economic partner and a wedge within NATO's cohesion. This study enhances the scholarly discourse by filling several key research gaps. It begins by offering a theoretical perspective based on realism and strategic hedging—an approach that remains underutilized in much of the prior, predominantly descriptive, literature. Furthermore, this study reveals that Türkiye’s foreign policy reflects a calculated strategy to navigate structural pressures while preserving autonomy. Empirically, the research examines bilateral interactions in Syria, Libya, Nagorno-Karabakh, and the Black Sea, highlighting how Türkiye and Russia manage conflictual interests through compartmentalized cooperation. It also addresses underexplored areas such as tourism and nuclear education as informal stabilizers in their relationship. Findings suggest that Türkiye’s engagement with Russia is not a deviation from its Western alliances, but part of a broader strategic hedge designed to enhance diplomatic flexibility. Likewise, Russia’s outreach to Ankara reinforces its goal of weakening transatlantic unity. Overall, the Türkiye–Russia relationship exemplifies pragmatic statecraft under multipolarity, where rivalry and cooperation coexist in a transactional equilibrium.